Clinical Predictive Factors Affecting Laparoscopic Approach in the Management of Ectopic Pregnancy: A Retrospective Cross-Sectional Study - Al-Husban, Naser; Thekrallah, Fida; Qatawneh, Aymen; Al-Ramahi, Dania; Al-Ashqar, Rama; Faraj, Balqees; Asfour, Mirona; Khreisat, Farah (Jordan Medical Journal, 2023)
Introduction: Ectopic pregnancy accounts for approximately 2% of all pregnancies and is the most common cause of pregnancy-related mortality in the first trimester. Our aim was to study the preoperative clinical factors affecting the choice of laparoscopic approach to tubal ectopic pregnancy. Materials and methods: This was a retrospective cross-sectional study of tubal ectopic pregnancy cases that were managed by laparoscopy at an academic university hospital in the period January 2010 to December 2018. Cases that were managed medically or conservatively and laparoscopic cases that were converted to laparotomy were excluded. Cases where the surgical approach of laparoscopy or laparotomy were determined by the patients’ choice were also excluded. Results: The laparoscopy rate was 49.4%. The mean age was 32.04 years. Compared with laparotomy, laparoscopy was significantly associated with low parity (less than 3) (p=0.008), a low level of initial beta-human chorionic gonadotrophin (p=0.032), fewer cases of adnexal mass (p=0.000451), hemoperitoneum (p=0.000072), ruptured ectopic (p=0.000261), and more cases of bowel adhesions (p=0.0095). There was no significant difference between laparoscopy and laparotomy regarding the risk factors of ectopic pregnancy. Salpingectomy and salpingostomy were not significantly different between the two surgical approaches (p=0.643). Twenty-eight laparoscopic cases were converted to laparotomy. Conclusion: The laparoscopic approach to ectopic pregnancy was affected by parity, presenting symptoms of pain and vomiting, mean initial beta-human chorionic gonadotrophin, the presence of adnexal mass, the presence of hemoperitoneum, and the rupture of the ectopic. Bowel adhesions were seen more frequently in laparoscopy than laparotomy. Salpingectomy and salpingostomy were no different between laparoscopy and laparotomy.